2004
DOI: 10.1079/bjn20041129
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic properties of the small intestinal and caecal contents of the chicken

Abstract: We measured the coefficients of viscosity, shear rates and shear stresses of chicken small intestinal and caecal contents, including solid particles, using a tube-flow viscometer. The coefficients of viscosity of chicken small intestinal and caecal contents were correlated negatively with their shear rates, a characteristic typical of non-Newtonian fluids. The coefficient of viscosity of the small intestinal contents was lower than that of the caecal contents at a shear rate of 1 s 21. Chicken caecal contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…The present study confirms the findings of previous studies1–4, 27 and suggests that insoluble fibres can be responsible for increasing digesta viscosity. The water‐holding capacity and/or swelling of insoluble fibres can elevate digesta viscosity by decreasing the free water content in digesta.…”
Section: Resultssupporting
confidence: 93%
“…The present study confirms the findings of previous studies1–4, 27 and suggests that insoluble fibres can be responsible for increasing digesta viscosity. The water‐holding capacity and/or swelling of insoluble fibres can elevate digesta viscosity by decreasing the free water content in digesta.…”
Section: Resultssupporting
confidence: 93%
“…Dusel et al (1997) observed a negative correlation between viscosity and apparent ME (AME) in 34 varieties of wheat fed to broilers, but no correlation between viscosity and AME in five varieties of wheat was observed by Svihus and Gullord (2002). It is likely that a lack of a correlation between viscosity and energy digestibility or concentration of DE and ME in pigs, as opposed to poultry, is a result of pigs being less affected by viscosity because poultry cecal contents are more viscous than in pigs (Thacker et al, 2002;Takahashi et al, 2004). Viscosity measurements may also be different before ingestion and at different points along the gastrointestinal tract due to potential depolymerization or reduction in electrostatic repulsion between polysaccharides (Guillon and Champ, 2000;Capuano, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, fluid mechanics dictate that, regardless of fill, the physical contact of digesta particles with any of these sites (Schalk and Amadon, 1928) is unlikely to occur when they are sufficiently dispersed in rumenal fluid to enable them to rotate and travel with their long axis oriented parallel to the line of flow i.e., exhibit shear thinning behaviour (Mongruel and Cloitre, 1999). Such shear thinning behaviour has been observed in fluid digesta from a number of herbivore species (Lentle et al., 2002, 2005; Takahashi and Sakata, 2004; Takahashi et al., 2004). Conversely, as the relative volume of digesta particles increases, they interact with each other to form a structure that behaves as an elastic solid (Lentle et al., 2005, 2009), can directly stimulate tactile receptors and is capable of sequestering finer particles (Lechner‐Doll et al., 1991).…”
Section: Introductionmentioning
confidence: 65%